2020
DOI: 10.46459/pmu.2020001
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral vector-mediated transfection of human cancer cell lines with tumor suppressor genes inhibits proliferation in vitro

Abstract: Background: Viral vector-mediated gene therapy has been eagerly studied as a new strategy for cancer treatment in recent years. We hypothesized that lentiviral vector-mediated gene therapy could be a promising strategy for the treatment of cancers that are highly refractory to chemotherapy or radiotherapy, such as malignant mesothelioma. In this study, we examined the effects of lentiviral vector-mediated transfection of tumor suppressor genes on the growth of malignant mesothelioma and other cancer cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…As of 2021, over 3,100 clinical studies on gene therapy have been conducted worldwide, 67.4% of which have targeted cancer 12 . Gene delivery techniques often use viral vectors, and we previously reported that the transduction of tumor suppressor genes using viral vectors in various cancer cells inhibits tumor cell proliferation 13 . However, there are significant legal and ethical hurdles and facility requirements to be addressed before gene therapy can be used in Japan, and it is extremely difficult to obtain approval for gene therapy under the current Japanese regulations.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2021, over 3,100 clinical studies on gene therapy have been conducted worldwide, 67.4% of which have targeted cancer 12 . Gene delivery techniques often use viral vectors, and we previously reported that the transduction of tumor suppressor genes using viral vectors in various cancer cells inhibits tumor cell proliferation 13 . However, there are significant legal and ethical hurdles and facility requirements to be addressed before gene therapy can be used in Japan, and it is extremely difficult to obtain approval for gene therapy under the current Japanese regulations.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2021, over 3,100 clinical studies on gene therapy have been conducted worldwide, 67.4% of which have targeted cancer [9]. Gene delivery techniques often use viral vectors, and we previously reported that the transduction of tumor suppressor genes using viral vectors in various cancer cells inhibits tumor cell proliferation [10]. However, there are signi cant legal and ethical hurdles and facility requirements to be addressed before gene therapy can be used in Japan, and it is extremely di cult to obtain approval for gene therapy under the current Japanese regulations.…”
Section: Introductionmentioning
confidence: 99%